Organometallic routes to colloidal nanomaterials for photoelectrochemical applications - Said, SA (2021)
This thesis describes the synthesis of inorganic semiconductor and layered zinc hydroxide colloidal nanomaterials that could, in future, be used in printing of photoelectrochemical devices. The colloidal nanomaterials are synthesised using organometallic precursors which are reacted with stoichiometric/sub-stoichiometric equivalents of ligand to provide well-defined, monodisperse, phase-controlled copper (Cu), cuprous oxide (Cu2O) and cuprous sulfide (Cu2S) nanoparticles or monolayer exfoliated layered zinc hydroxide (LZH) nanosheets.